2019
DOI: 10.1177/1457496919832147
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Gallstone Disease in the Elderly Population: Outcomes and Recurrence

Abstract: Background & Aims: The prevalence of gallstone disease increases with age, being early cholecystectomy the most accepted treatment in the vast majority of patients in order to prevent complications and recurrence. The aim of this study is to determine the recurrence rate and its possible predictors after initial non-operative management. Materials and Methods: We reviewed a consecutive series of patients, older than 65 years, admitted for a gallstone-related disease and treated with a non-operative managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Laparoscopic cholecystectomy (LCC) is a common procedure performed by gastrointestinal (GI) surgeons, and several reports recommend early cholecystectomy for acute cholecystitis (1)(2)(3)(4). LCC for acute cholecystitis is associated with a higher risk of conversion compared with elective LCC, since the inflamed tissues and the distorted anatomy might prove an obstacle too hard to overcome laparoscopically.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy (LCC) is a common procedure performed by gastrointestinal (GI) surgeons, and several reports recommend early cholecystectomy for acute cholecystitis (1)(2)(3)(4). LCC for acute cholecystitis is associated with a higher risk of conversion compared with elective LCC, since the inflamed tissues and the distorted anatomy might prove an obstacle too hard to overcome laparoscopically.…”
Section: Introductionmentioning
confidence: 99%
“…cholecystectomy. Many studies evaluating outcomes of laparoscopic cholecystectomy in their definition of elderly patients versus younger patients have shown that increasing age leads to higher conversion rates, more complications and a longer hospital stay [7][8][9][10].…”
mentioning
confidence: 99%
“…With an ageing population, demands for surgery are expected to rise over the next decade with associated increasing frailty [ 5 , 6 ]. In parallel, it is estimated that increasing numbers of elderly patients will present with gallstone disease [ 7 , 8 ], and it is thought that patients aged 80–89 years account for 28% and 42% of male and female patients, respectively [ 8 , 9 ]. Since age is associated with existence of multiple comorbidities and reduced functional reserve, it is thought that operating on elderly patients could be associated with an increased risk of complications [ 10 12 ].…”
mentioning
confidence: 99%
“…The elderly were commonly seen with gallstone disease; this was attributed to the aging and sedentary lifestyle of the elderly population. Similarly, Mora-Guzmán et al revealed that elderly patients were at a higher risk of developing gallstones and gallstone-related complications along with recurrence of gallstones in one-third of patient follow-ups [ 17 ].…”
Section: Discussionmentioning
confidence: 99%